Editorial: SPECIAL ISSUE: SOCIAL APPROACHES TO HIV/AIDS - Campbell, Catherine; Hayes, Grahame (PINS-Psychology in Society, 2026)
The aim of this special issue of PINS, entitled social approaches to HIV/AIDS, has been to highlight some of the conceptual tools which social psychology provides in the task of advancing our understandings of sexualities and health. Social scientific research into HIV/AIDS could be significantly enhanced through a more intensive engagement with the rich tapestry of theoretical debates which already characterise social psychology. It is hoped that the contributions to this special of PINS begin to highlight the importance of theoretical frameworks for understanding the complexity of HIV/AIDS, and consequently produce more finely tuned intervention programmes.